2014
DOI: 10.1088/1367-2630/16/1/013017
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional simulations of temperature and current-density distribution in electromigrated structures

Abstract: We report on the application of a feedback-controlled electromigration technique for the formation of nanometre-sized gaps in mesoscopic gold wires and rings. The effect of current density and temperature, linked via Joule heating, on the resulting gap size is investigated. Our experiments include in situ measurements of the evolution of the electrical resistance and of the structure of the device during electromigration. Experimentally, a good thermal coupling to the substrate turned out to be crucial to reac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…The thermal conductivity of the substrate is an important parameter for successful controlled electromigration [26,27]. We use sapphire as a substrate due to its large heat conductivity (30.3 W (m K) -1 ) perpendicular to the c-axis and 32.5 W (m K) -1 parallel to the c-axis [28].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The thermal conductivity of the substrate is an important parameter for successful controlled electromigration [26,27]. We use sapphire as a substrate due to its large heat conductivity (30.3 W (m K) -1 ) perpendicular to the c-axis and 32.5 W (m K) -1 parallel to the c-axis [28].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, in many cases, heat conduction through the substrate plays a role. A number of efforts have been made to measure (Holm, 1967 andWard et al, 2008) and calculate the temperature distribution of the device (Durkan, 2007;Kiessig et al, 2014;and Cornelius et al, 2008) in more detail. Durkan (2007) used a one-dimensional model where it is assumed that heat is created by Joule heating at the same rate everywhere in the wire.…”
Section: A Local Temperature Distributionmentioning
confidence: 99%
“…38. By a careful comparison of measurements and simulations, it can be shown that a good thermal coupling to the substrate plays an important role in the temperature balance (Durkan et al, 1999;Kiessig et al, 2014;and Yang et al, 2005).…”
Section: A Local Temperature Distributionmentioning
confidence: 99%
“…In general, a direct comparison of TEM studies to our experiment is difficult since for in-situ TEM studies, samples have to be prepared on very thin substrates. The thickness of the substrate, by virtue of its thermal conductance, is known to have a significant influence on the effective temperature profile along the nanobridge during the EM 15,16 . This temperature profile is decisive because different temperatures during the process may result in different structural changes and gap formations.…”
mentioning
confidence: 99%